One Stone, Two Birds: The Roles of Tim-3 in Acute Myeloid Leukemia - Wang, Zhiding; Chen, Jinghong; Wang, Mengzhen; Zhang, Linlin; Yu, Li (Frontiers in Immunology, 2021)
T cell immunoglobulin and mucin protein 3 (Tim-3) is an immune checkpoint and plays a vital role in immune responses during acute myeloid leukemia (AML). Targeting Tim-3 kills two birds with one stone by balancing the immune system and eliminating leukemia stem cells (LSCs) in AML. These functions make Tim-3 a potential target for curing AML. This review mainly discusses the roles of Tim-3 in the immune system in AML and as an AML LSC marker, which sheds new light on the role of Tim-3 in AML immunotherapy.